HIP 60350: A supernova ejected hyper-runaway star? - Irrgang, Andreas; Przybilla, Norbert; Heber, Ulrich; Nieva, M. Fernanda; Schuh, Sonja (Proceedings of Science, 2010)
Halo runaway stars, i.e., young, massive, high-velocity stars in the halo of our Galaxy, are widely supposed to be the result of an ejection event from the Galactic disk. The three most likely ejection scenarios are tidal disruptions of binary systems by the supermassive black hole at the Galactic center, dynamical interactions in star clusters, e.g., binary-binary encounters, or a supernova explosion disrupting a binary system. Here, we present a detailed spectroscopic and kinematic analysis of the runaway B star HIP 60350 to discuss the three competing mechanisms. Using spectrum synthesis techniques that allow for deviations from local thermal equilibrium, we derived chemical elemental abundances from high resolution spectra. The analysis of HIP 60350 revealed an outstanding high Galactic rest-frame velocity of 530±35kms-1 slightly exceeding the local Galactic escape velocity and thus qualifying the star as a hyper-runaway candidate, i.e., an unbound runaway star. The kinematically predicted birthplace within the disk is located ∼ 6kpc away from the Galactic center excluding this region as the star's spatial origin and in this way the involvement of the central supermassive black hole. Instead, the obtained chemical abundance pattern shows hints of α-element enhancement being characteristic of supernova debris. HIP 60350 might be the surviving secondary of a massive, close binary system disrupted by the primary's supernova explosion. © Copyright owned by the author(s).
CRIS-Team Scopus Importer:2020-12-21